A WAY TO A SUSTAINABLE FUTURE: THE SOLAR INDUSTRY IN JAPAN - Varvara V. Akimova; Irina S. Tikhotskaya (Geography, Environment, Sustainability)
Solar energy is considered one of the most promising and rapidly growing sectors of the world economy. In line with the international trend of switching to renewable energy sources, particularly solar, and because of the tragic events at the Fukushima nuclear power station, Japan is experiencing a real “solar boom.” However, despite all obvious advantages of using solar power (ensuring national energy security, overcoming concerns about environmental consequences of using fossil energy sources, etc.), Japan is facing several problems in its development. The most important one is the fact that technological and social progresses in Japan do not match each other as a result of a unique history of the nation. In order to promote renewable technology, the emphasis should be made on the role of the governmental policy and the effects of built-in tariffs for renewable energy sources. Considering dynamics and character of solar energy development in Japan, new energy strategy, and megasolar plants construction, the conclusion might be drawn that in the nearest future Japan will keep its place among the leaders in this field.